2011
DOI: 10.1007/s12144-011-9118-x
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effect of Parental Education on Language Production

Abstract: This study examines the interactive effect of mother's and father's education on childhood language development. Parents of sixteen-and twentymonth-old children (N=48) completed measures on their children's language production (MacArthur Communicative Development Inventory: Words and Sentences) as well as basic demographic information. There were variations in language production according to maternal education for only the older children. There was also an interaction between maternal and paternal education; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…They found that children spending 40 hours or more in daycare per week and had fathers with a high educational background, outperformed children with fathers with a lower educational level on expressive vocabulary scores (p. 592). In addition, the interaction between different levels of maternal and paternal education should be considered (Hupp et al, 2011). Hupp et al (2011) found that children with parents who had heterogeneous levels of parental education (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that children spending 40 hours or more in daycare per week and had fathers with a high educational background, outperformed children with fathers with a lower educational level on expressive vocabulary scores (p. 592). In addition, the interaction between different levels of maternal and paternal education should be considered (Hupp et al, 2011). Hupp et al (2011) found that children with parents who had heterogeneous levels of parental education (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the interaction between different levels of maternal and paternal education should be considered (Hupp et al, 2011). Hupp et al (2011) found that children with parents who had heterogeneous levels of parental education (e.g. one parent without a degree, one with a degree), attained higher language production scores.…”
Section: Discussionmentioning
confidence: 99%
“…Low parental education, as an indicator of SES, is reported to predict language difficulties in children [ 40 ]. Hupp and colleagues [ 31 ] found that twenty-month-old children with well-educated mothers demonstrated better language production skills compared to those whose mothers were not as well-educated. Furthermore, variations in language exposure (e.g.…”
Section: Introductionmentioning
confidence: 99%